Population genomics of sika deer reveals recent speciation and genetic selective signatures during evolution and domestication - Huamiao Liu; Bo Zhu; Tianjiao Wang; Yimeng Dong; Yan Ju; Yang Li; Weilin Su; Ranran Zhang; Shiwu Dong; Hongliang Wang; Yongna Zhou; Yanmin Zhu; et al. (BMC Genomics)
Abstract Background Population genomic analysis can reconstruct the phylogenetic relationship and demographic history, and identify genomic selective signatures of a species. To date, fundamental aspects of population genomic analyses, such as intraspecies taxonomy, evolutionary history, and adaptive evolution, of sika deer have not been systematically investigated. Furthermore, accumulating lines of evidences have illustrated that incorrect species delimitation will mislead conservation decisions, and even lead to irreversible mistakes in threatened species. Results In this study, we resequenced 81 wild and 71 domesticated sika deer representing 10 main geographic populations and two farms to clarify the species delimitation, demographic and divergence histories, and adaptive evolution of this species. First, our analyses of whole genomes, Y chromosomes and mitochondrial genomes revealed substantial genetic differentiation between the continental and Japanese lineages of sika deer, representing two phylogenetically distinct species. Second, sika deer in Japan were inferred to have experienced a “divergence-mixing-isolation” evolutionary scenario. Third, we identified four candidate genes (XKR4, NPAS3, CTNNA3, and CNTNAP5) possibly involved in body size regulation of sika deer by selective sweep analysis. Furthermore, we also detected two candidate genes (NRP2 and EDIL3) that may be associated with an important economic trait (antler weight) were under selection during the process of domestication. Conclusion Population genomic analyses revealed that the continental and Japanese lineages represent distinct phylogenetic species. Moreover, our results provide insights into the genetic selection signatures related to body size differences and a valuable genomic resource for future genetic studies and genomics-informed breeding of sika deer.